(untitled) (Olhar de Professor, 2011)
This article discusses the process of learning to teach of seven graduate and non-graduate teachers of the preparatory entrance exam of the Federal University of Sao Carlos (UFSCAr) with the aim of understanding the kind of learning that takes place during teaching. The investigation was based on studies about teacher education that view learning to teach as a continuous process that involves reflection during practice, about the teaching practice and its context. Questionnaires and interviews were used with teachers in order to understand how they see their own practice. The results show that teachers change their teaching according to students´ demands and according to the analysis of their experiences in contexts such as the preparatory entrance exam that due to their management and organization go beyond the classroom.